Primary liver cancer and renal cell carcinoma in laundry and dry-cleaning workers in Denmark - Lynge, Elsebeth; Carstensen, B.; Andersen, O. (Scandinavian Journal of Work, Environment & Health, 1995)
' ' OBJECTIVES ': 'Previous studies have shown an excess risk of primary liver cancer among women working in laundries and dry-cleaning shops in Denmark at the time of the census in 1970. During the period 1970--1987, 14 cases of primary liver cancer were observed (standardized mortality ratio 2.7, 95% confidence interval 1.5--4.5). A nested case-referent study was undertaken in order to classify laundry workers and dry-cleaning workers separately. According to hints in the literature, renal-cell carcinomas were also included in this analysis.' ' METHODS ': 'Original census forms from 1970 were retrieved from the Danish National Record Office for the 17 cases with primary liver cancer and the 16 cases with renal-cell carcinoma and five matched referents per case.' ' RESULTS ': 'All of the 17 patients with primary liver cancer worked in laundries in 1970, whereas only 74% of the referents worked in laundries. Neither was the risk of renal-cell carcinoma associated with dry-cleaning work (relative risk 0.7, 95% CI 0.2--2.6).' ' CONCLUSION ': 'The excess risk of primary liver cancer observed for women working in laundries and dry-cleaning shops in Denmark is not likely to be explained by exposure to dry-cleaning solvents. Excessive alcohol consumption is not a likely explanation either, and the excess risk therefore remains unexplained.
Keywords: cancer incidence; control study; nested case-referent study; occupational health